letter of the Governor of the central bank of egypt concerning the import transactions regulations - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
letter of the Governor of the central bank of Egypt concerning the import transactions regulations – كتاب دورى البنك المركزى بتاريخ 22 فبراير 2016 بشأن ضوابط العمليات الاستردادية